Prevalence and factors of physical punishment and psychological aggression toward children under five in Mongolia: an analysis of the 2018 Social Indicator Survey - Anujin Enkhbat; Seungman Cha; Ermias Tadesse Beyene; Yan Jin (Global Health Action)
Background The global prevalence of violence against children is alarmingly high, with millions facing violent discipline and physical punishment. In Mongolia, domestic violence-related criminal offenses have sharply increased, with a 46.92% surge in the first quarter of 2020 compared to 2019. Objective This study aimed to estimate the prevalence of and identify factors associated with physical punishment and/or psychological aggression experienced by children under 5 years old from their caregivers. Methods We used data from the nationally representative 2018 MICS6 dataset. To examine the association between independent and dependent variables, we used multilevel Poisson regression because it provides a better estimate and is more interpretable when the prevalence is relatively high. Results The prevalence of psychological aggression was reported at 32.3% and physical punishment at 31.6%, including severe forms. Nonviolent techniques were common, with 77.5% exclusively using nonviolent discipline. Psychological aggression was more likely to occur in older children (3 and 4 years old) and in households with Buddhist heads. Additionally, 3-year-olds are more likely to experience physical punishment compared to 2-year-olds. Conclusion These findings underscore the need for targeted policy interventions, including age-sensitive parental education programs and religious and cultural sensitivity measures. Comprehensive educational and awareness programs are essential to foster a culture of nonviolence across all educational levels, highlighting the need for context-specific policies to safeguard the well-being of children in Mongolia.